Sedative effect of freshly crushed young guava leaves on acute dental pain - Centeno, Maria Liza C.
This seminar paper aims to determine the sedative capacity of freshly crused young guava leaves (FCYGL) on acute dental pain. A placebo and FCYGL were administered to teeth experiencing acute dental pain and pulp exposure. Only teeth with pulp exposure were included in this study - to eliminate variations in the thickness of dentin to the pulp, therefore with this qualification, the investigators felt that the sedative property of FCYGL could be better analyzed. To determine whether the FCYGL exerted sedative effect on the exposed pulp, the patients were asked if they experienced any relief of pain. Those who felt a slight to complete relief of pain were recorded under the "YES" category and those who did not feel any relief whatsoever were placed under the "No" category. Statistical analysis was based on the Yes and No responses of the patients. Those who responded positively to the placebo were automatically disqualified from the study. The results gathered in this investigation shows that FCYGL may have a potential sedative capacity since statistical tests prove a significant difference between those who felt relieved and those who did not.